Clinical effects of CD33 and MPC-1 on the prognosis of multiple myeloma treated with bortezomib. Issue 9 (29th July 2019) - Oka, Satoko; Ono, Kazuo; Nohgawa, Masaharu
Abstract: In the present study, the effects of immunophenotyping on the prognoses of patients with MM treated with bortezomib as induction therapy were investigated. A total of 118 patients with MM were examined, and the prognostic significance of the immunophenotyping and other factors were investigated. Immature and plasmablastic cell types and high-risk cytogenesis were more frequently observed in patients with CD33+ and MPC-1−. CD33+ and MPC-1− have potential as prognostic factors and correlated with lower progression-free survival and overall survival in a Kaplan–Meier analysis. Moreover, the present results demonstrated that at the relapse of disease, the percentage of CD33 increased (median 48.7%) and MPC-1 decreased (median 14.1%), respectively, therefore, both of these antigens may be associated with the refractory disease status. The present study showed that the expression of CD33 and MPC-1 in neoplastic plasma cells from patients with MM was associated with patient prognosis independent of other prognostic factors.